Legal aspects of gender identity in Ukraine - Piddubnyi, Oleksii Yu.; Marits, Dariia O.; Yehorova, Valentyna S.; Chepulchenko, Tetiana O.; Vladykin, Oleksandr N. (Linguistics and Culture Review, 2021)
The issue of gender identity in the modern world is becoming increasingly relevant. The place of a person's right to recognise their gender identity in the Ukrainian legal plane is uncertain. The study considers the specific features of regulating the human right to recognise gender identity and gender reassignment in Ukraine. The authors of the study consider personal non-property rights of an individual as a specific concept, and somatic rights – as a generic concept, the main meaning of which is the ability to dispose of one's body. Accordingly, a person's right to recognition of their gender identity is a personal non-property right. In Ukraine, legal regulation of gender change is carried out, but certain regulations come into force only in the event of a legal fact of gender change, although their provisions regulate the direct implementation of such a right. However, gender identity is the third most common cause of discrimination. It is necessary for Ukrainian legislation to update the regulatory framework that governs the procedure for changing gender. It is worth paying attention to the correct use of terminology in these relations.